Leak Monitoring Prototype and Gas Availability in CO2 Type APAR (Light Fire Extinguisher) - Huda, Samsul; Ilmi , Muh. Bahrul (Universitas Panca Marga, 2022)
Fire safety is an important aspect that must be considered when in a building. A lightweight fire extinguisher (APAR) is a piece of mandatory standard equipment for building safety. Therefore, it requires maintenance operations to ensure the fire extinguisher is functioning properly whenever needed. This monitoring activity is still done manually with human power. Moreover, these standard controls and checks are often neglected. In this study, we propose a prototype of the gas availability monitoring system for CO2-type fire extinguishers. We adopt NodeMCU esp8266 as processor, gas sensor as CO2 reader and buzzer as output. This design serves to detect the level of CO2 concentration around the location of the extinguisher tube placement. The system will also sound a buzzer and send a notification via telegram when the CO2 concentration reading is not within the normal range, which means a gas leak has occurred. Features and services have been validated through two test scenarios